High-density reflection spectroscopy: I. A case study of GX 339-4. Issue 2 (10th January 2019) - Jiang, Jiachen; Fabian, Andrew C; Wang, Jingyi; Walton, Dominic J; García, Javier A; Parker, Michael L; Steiner, James F; Tomsick, John A
ABSTRACT: We present a broad-band spectral analysis of the black hole binary GX 339-4 with NuSTAR and Swift using high-density reflection model. The observations were taken when the source was in low-flux (LF) hard states during the outbursts in 2013 and 2015, and in a very high-flux (HF) soft state in 2015. The high-density reflection model can explain its LF spectra with no requirement for an additional low temperature thermal component. This model enables us to constrain the density in the disc surface of GX 339-4 in different flux states. The disc density in the LF state is log ( n e / cm −3 ) ≈ 21, 100 times higher than the density in the HF state (log ( n e / cm$^{-3})=18.93^{+0.12}_{-0.16}$ ). A close-to-solar iron abundance is obtained by modelling the LF and HF broad-band spectra with variable density reflection model ($Z_{\rm Fe}=1.50^{+0.12}_{-0.04}\text{Z}_{\odot}$ and $Z_{\rm Fe}=1.05^{+0.17}_{-0.15}\text{Z}_{\odot, }$, respectively).